Arduino-based Automatic Fish Feeding Device Prototype - Muhammad Iqbal Nugraha; Bagus Dwi Cahyono (Journal of Computer Science Advancements, 2023)
Consuming fish food is an important part of the process of growing and maintaining fish. In general, fish food is given by conventionally throwing it by hand. However, this is not done at the same time every day. Based on the problems above, the researchers made a prototype of an Arduino-based automatic fish feeding device. The aim of this research is to determine the effectiveness of the automatic fish feeder prototype. In the prototype that the researchers made using several main components such as Arduino Uno as the system or brain of this prototype, servo motor, 20 x 4 LCD, buttons, Real Time Clock (RTC), and several jumper cables. The effectiveness of this tool can be seen from the test results, where the automatic fish feeder prototype succeeded in providing fish food according to a predetermined schedule.